CRITERIA FOR ASSESSING THE USE OF HUMAN CAPITAL IN SMALL BUSINESS - Olimov Furqat Khoshimovich (American Journals, 2023)
The article deals with the concept of human capital, the history of its emergence, the opinions of world scientists about this theory, and the role of human capital in achieving sustainable economic development in the country.
Keywords: assessment, investment, human capital, economic stability, social needs, knowledge, skills, human resources.